Pemberian Kalsium Karbonat CaCO3 pada Media Bersalinitas 3 g L-1 Untuk Pertumbuhan Ikan Sepat Siam Trichopodus pectoralis - Hastuti, Yuni Puji; Mahmud, Moh Burhanuddin; Anwar, Rifky Alwafi; Supriyono, Eddy; Nirmala, Kukuh; Nurussalam, Wildan (Universitas Batangahari Jambi, 2025)
The snakeskin gourami is a part of the superior commodity of freshwater fisheries in Indonesia because it has economic value and high demand. Technology is needed to optimize the growth of snakeskin gourami so that the production of snakeskin gourami from aquaculture becomes more stable. The method of adding calcium to the salinity water is a part of the technology to optimize the growth of cultured fish. The purpose of this research is to determine the best amount of CaCO3 calcium carbonate lime on the growth of snakeskin gourami that are maintained at 3 g L-1 of salinity. The tank is used in the form of an aquarium measuring 30x30x30 cm3 with a volume of water as much as 20 liters. The snakeskin gourami used were 8.7 ± 0.46 cm in length and weighed 8.3 ± 1.37 g. The fish are fed with the restricted method (5% of fish biomass). The study was conducted by applying calcium carbonate CaCO₃ at concentrations of 50, 100, 150, and 200 mg L⁻¹, with an additional control treatment that received no calcium carbonate application. The results showed that the best amount of CaCO3 calcium carbonate lime, as much as 100 mg L-1, showed 2.5 cm of total length growth, total weight growth of 6.35 g, daily growth rate of 2%, and survival rate of 93.3%. The best amount of CaCO3 calcium carbonate lime for 3 g L-1 of salinity water is 100 mg L-1. The best amount of CaCO3 calcium carbonate lime for the growth of snakeskin gourami that is maintained at 3 g L-1 of salinity is 100 mg L-1.